Comparative assessment of the design of tubular elements according to offshore design standards and Eurocode 3. Issue 4 (November 2016) - Manco, Tiago; Rigueiro, Maria Constança; Martins, João Pedro; da Silva, Luís Simões
Abstract: Steel circular tubular elements are among the most commonly used types of structural element in offshore structures. The objective of this paper is to perform a comparative analysis of design standards for offshore structures with a focus on the structural design of these elements. The intention is to reach a conclusion about the level of safety that offshore and construction standards provide regarding the design of tubular circular elements. To this end, the bearing capacity obtained with ISO 19902 and Eurocode 3 (which does not contain specific provisions for offshore structures) parts 1‐1 and 1‐6 will be compared in a broad parametric study. Subsequently, the accuracy and level of safety that ISO and EC3 assume are assessed through numerical analysis using the ABAQUS software. The performance of a set of steel circular tubular elements is evaluated under axial compression and hydrostatic pressure. Finally, the interaction between axial compression and hydrostatic pressure is also analysed.